A novel determination of energy expenditure efficiency during a balance task using accelerometers. A pilot study. Issue 2 (15th March 2019) - Caña-Pino, Alejandro; Apolo-Arenas, Maria Dolores; Moral-Blanco, Javier; De la Cruz-Sánchez, Ernesto; Espejo-Antúnez, Luis
ABSTRACT: The objectives of this study are to determine the displacement of the center of pressure (CoP) and its association with the spectral energy density of the acceleration required for the maintenance of postural balance in different standing positions in healthy participants using design observational and setting laboratorial studies. Participants were 30 healthy university students aged between 18 and 32 years old (mean [M] ± standard deviation [ SD ] = 21, 57 ± 3, 31 years). Triaxial accelerometer and a pressure platform were used in order to obtain energy spectral density and CoP sway measurements during four balance tasks. Statistically significant differences were found for anteroposterior ( p = 0.002) and mediolateral ( p = 0.009) CoP displacement between the conditions eyes closed and stable surface and the conditions eyes closed and unstable surface. A statistically significant correlation was also observed between Z-axis (anterior-posterior) of the accelerometer and mediolateral axis of the CoP ( r = 0.465; p = 0.01) and between Y-axis accelerometer (mediolateral) and displacement of the CoP in the anteroposterior axis ( r = 0.413; p = 0.023). Spectral energy density appears to be associated with the displacement of CoP in healthy participants.